GREEN DARNER ALGORITHM FOR SOLVING OPTIMAL POWER FLOW PROBLEM - Lenin, K. (International Journal of Research -GRANTHAALAYAH, 2017)
In this paper a Green Darner (GD) algorithm is used to solve optimal reactive power problem. The key inducement of the Green Darner (GD) algorithm initiated from inert and vibrant swarming behaviors. These two swarming behaviours are very similar to the two key segment of optimization using meta-heuristics: exploration and exploitation. Green Darner (GD) engenders sub swarms and flies over assorted areas in an inert swarm, & it will be the main goal of the exploration segment. In the inert swarm, conversely, Green Darner (GD) flies in bigger swarms and down to one direction, which is constructive in the exploitation segment. In this proposed Green Darner (GD) algorithm, two necessary segments of optimization, exploration and exploitation, are planned by modeling the social communication of Green Darner (GD) in navigating, probing for foods, and keep away from enemies when swarming vigorously or statistically. The projected Green Darner (GD) algorithm has been tested in standard IEEE 118 & practical 191 bus test systems and simulation results show clearly about the improved performance of the projected Green Darner (GD) algorithm in reducing the real power loss.